Contribution of FGFR1 Variants to Craniofacial Variations in East Asians - Adel, Mohamed; Yamaguchi, Tetsutaro; Tomita, Daisuke; Nakawaki, Takatoshi; Kim, Yong-Il; Hikita, Yu; Haga, Shugo; Takahashi, Masahiro; Nadim, Mohamed A.; Kawaguchi, Akira; Isa, Mutsumi; El-Kenany, Walid H.; et al. (PloS one, 2017)
FGFR1 plays an important role in the development of the nervous system as well as the regulation of the skeletal development and bone homeostasis. Mutations in FGFR1 genes affect skull development, specifically suture and synchondrosis, resulting in craniosynostosis and facial abnormalities. We examined subjects with normal skull morphology for genetic polymorphisms that might be associated with normal craniofacial variations. Genomic DNA was obtained from 216 Japanese and 227 Korean subjects. Four FGFR1 SNPs, namely, rs881301, rs6996321, rs4647905, and rs13317, were genotyped. These SNPs were tested for association with craniofacial measurements obtained from lateral and posteroanterior cephalometries, in which principle component analysis was performed to compress the data of the craniofacial measurements. We observed that SNPs rs13317 and rs6996321 were correlated with the overall head size and midfacial development, indicating that FGFR1 SNPs played crucial roles in the normal variation of human craniofacial morphology. Subjects with the derived alleles of SNPs rs13317 and rs6996321 had a small face and a facial pattern associated with a retruded midface and relatively wide-set eyes. These facial features were similar to but were milder than those of individuals with Pfeiffer syndrome, which is caused by a dysfunctional mutation in FGFR1.